Asymmetric distribution of G-quadruplex forming sequences in genomes of retroviruses - Kledus, Filip; Dobrovolná, Michaela; Mergny, Jean-Louis; Brázda, Václav (Scientific reports, 2025)
Retroviruses are among the most extensively studied viral families, both historically and in contemporary research. They are primarily investigated in the fields of viral oncogenesis, reverse transcription mechanisms, and other infection-specific aspects. These include the integration of endogenous retroviruses (ERVs) into host genomes, a process widely utilized in genetic engineering, and the ongoing search for HIV/AIDS treatment. G-quadruplexes (G4) have emerged as potential therapeutic targets in antiviral therapy and have been identified in important regulatory regions of viral genomes. In this study, we examine the presence of potential G-quadruplex-forming sequences (PQS) across all currently available unique retroviral genomes. Given that these retroviral genomes typically consist of single-stranded RNA (ssRNA) molecules, we also investigated whether the localization of PQSs is strand-dependent. This is particularly relevant since antisense transcripts have been detected in HIV, and ERV integration into the host genome involves reverse transcription from genomic positive strand ssRNA to double-stranded DNA (dsDNA), implicating both strands in this process. We show that in most mammalian retroviruses, including human retroviruses, PQSs are significantly more prevalent on the negative (antisense) strand, with some notable exceptions such as HIV-1. In sharp contrast, avian retroviruses exhibit a higher prevalence of PQSs on the positive (sense) strand.
Keywords: Retroviridae; Endogenous Retroviruses; Animals; genom virový; Bioinformatics; G-kvadruplexy; lidé; Genome, Viral; zvířata; endogenní retroviry; G-Quadruplexes; Retroviral genome; G4Hunter; Persistent infection; G-quadruplex; Humans